Pressure Ulcers on Admission to Palliative Care Unit and Scores on Norton and Braden Scales - Hilal Zengin; İlker Taşçı (Galenos Yayinevi, 2023)
Objective: Pressure ulcers (PU) are common in patients admitted to palliative care clinics (PCC). Pregressive nutritional deficiency, incontinence, and limitation of movement increase the risk of new PU formation. Purpose: To examine the risk of PU in patients hospitalized in PCC andthe rate of wounds on admission. Materials and Methods: We retrospectively analyzed patients hospitalized between 2017 and 2019 in a PCC integrated into a tertiary health institution. Patients with demographic and clinical data, data on the region, number, and stage of PU, and Norton and Braden pressure risk scores were enrolled. Patients with scores 11 on the Norton scale and 18 on the Braden scale were considered to be at higher risk for PU. Results: The final analysis included 566 patients [mean age: 68 years, male: 328 (58%)]. On admission, PU was recorded in 181 patients (32%) (sacrum: 80%). According to the Norton scale, 269 (47.5%) of all cases were under the risk of PU and 48.7% (n=131) of them already had PU. According to the Braden scale, 475 (83.9%) patients were at risk of PU, and 37.5% (n=178) of them already had PU. Among subjects with a low Norton score (n=297), 16% (n=50) already had PUs. Among subjects with PUs, the Norton score was not high 27.6%. Only 3.3% (n=3) of 91 patients whose Braden score was not low already had a PU. The sensitivity and specificity of the Norton score in the prediction of PU were 48.9% and 83.2%, respectively. The sensitivity and specificity of the Braden score in the prediction of PU were 66.9% and 99.0%, respectively. Conclusion: Physical PU examination on admission to PCC and during follow-up can identify a significant number of cases. The utility of Norton and Braden scores to estimate the occurrence of PUs may be limited in the palliative care setting or patients.